Childhood and the opinions of Western religious scholars and scholars (Journal of Misan Researches, 2022)
In this research, we address the views of Islamic scholars on the one hand, and Western scholars on the other hand, by comparing the two opinions on the psychology of childhood. We have chosen two scholars from among Islamic scholars: Ibn Sina and Ibn Khaldun. And the stage of cradle and breastfeeding, the stage of early childhood, the stage of middle childhood, and finally the stage of puberty, and he studied each stage separately. As for Ibn Khaldun, He did not treat the childhood stage in terms of formation and growth, and he did not divide it as Ibn Sina did, but he looked at it from an educational and educational point of view, and the most prominent of his books that dealt with this subject is the Introduction. As for Western scholars, we have discussed the views of Freud, Orla Nesky, and Johnson, and Freud had divided childhood into stages: the oral stage, the anal stage, the stage of sexual regions, the latency stage, and the adult sexual stage, and it is a successful example of the way Western scholars deal with childhood Therefore, our research consisted of two demands, and we distributed them to the opinions of scholars: Islamists and Westerners.